Biotransformation of Scheelite CaWO4 by the Extreme Thermoacidophile Metallosphaera sedula: Tungsten–Microbial Interface - Blazevic, Amir; Albu, Mihaela; Mitsche, Stefan; Rittmann, Simon K.-M. R.; Habler, Gerlinde; Milojevic, Tetyana (Frontiers in Microbiology, 2019)
The tungsten-microbial interactions and microbial bioprocessing of tungsten ores, which are still underexplored, are the focus of the current study. Here we show that the biotransformation of tungsten mineral scheelite performed by the extreme thermoacidophile Metallosphaera sedula leads to the breakage of scheelite structure and subsequent tungsten solubilization. Total soluble tungsten is significantly higher in cultures containing M. sedula grown on scheelite than the abiotic control, indicating active bioleaching. Advanced analytical electron microscopy was used in order to achieve nanoscale resolution ultrastructural studies of M. sedula grown on tungsten bearing scheelite. In particular, we describe that M. sedula mediated the biotransformation of scheelite, which was accompanied by the release of tungsten into solution and tungsten biomineralization of the cell surface. Furthermore, we observed intracellular incorporation of redox heterogenous Mn- and Fe-containing nano-clusters. Our results highlight unique metallophilic life in hostile environments extending the knowledge of tungsten biogeochemistry. Based on these findings biohydrometallurgical processing of tungsten ores can be further explored. Importantly, biogenic tungsten carbide-like nanolayers described herein are potential targets for developing nanomaterial biotechnology.